Design and characterization of frequency reconfigurable honey bee antenna for cognitive radio application - Abu Hena Murshed; Md. Azad Hossain; Eisuke Nishiyama; Ichihiko Toyoda (Institute of Advanced Engineering and Science, 2022)
In this article, a frequency reconfigurable honey-bee compact microstrip monopole antenna is proposed which is fed by a microstrip line (50 Ω) having the capability of providing dual-band as well as triple-band operation in eight distinct modes. By embedding three PIN diodes overs the honey bee arms, the effective current distribution is controlled hence resonant frequency is also changed in eight distinct modes in real-time. This is the reason the proposed antenna is portrayed as a frequency reconfigurable antenna in this paper which is suitable for cognitive radio application. This proposed antenna can be used for various wireless application such as Bluetooth, Wi-Fi, worldwide interoperability for microwave access (WiMAX), wireless local area network (WLAN), C-band, and X-band applications. The proposed antenna possesses a planner geometry of 39×34×0.87 mm3 which is printed on a substrate as flexible FR-4 (lossy) (εr=4.4 and tanδ=0.019). The proposed antenna exhibits voltage standing wave ratio (VSWR)<2 for all 19 resonant frequencies of interest and perceptible radiation pattern over entire frequency bands with a positive gain. CST microwave studio is used to find out all simulated results of antenna parameters.